2020
DOI: 10.1111/tog.12704
|View full text |Cite
|
Sign up to set email alerts
|

Raised CA125 what we actually know…

Abstract: Carbohydrate antigen 125 (CA125) is an antigen used in the diagnosis of epithelial nonmucinous ovarian cancers. CA125 may be elevated in many benign and malignant conditions, so elevated levels can cause confusion over patient management. The multidisciplinary team is important when planning care for patients with suspected ovarian cancer. Learning objectivesTo know the factors leading to CA125 production and its mechanism of action.To understand how CA125 is used as a diagnostic tool and to assess the treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…Ca-125 levels can increase in both physiological and pathological conditions such as the menstrual cycle, first trimester pregnancy, ovarian carcinoma, fibroids, endometriosis, pelvic inflammatory disease, benign ovarian cysts, hepatitis, ascites, pleural effusions and lymphangioleiomyomatosis (LAM) 11 12. It has been suggested that Ca-125 is synthesised in the mesothelial cells as a stress response to either fluid congestion (mechanical stress) or cell mediators (inflammatory stress) 13. Howe et al comment on the importance of understanding how these biological mechanisms correlate with a wide range of conditions, for clinicians who are assessing the significance of elevated Ca-125 levels 13.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ca-125 levels can increase in both physiological and pathological conditions such as the menstrual cycle, first trimester pregnancy, ovarian carcinoma, fibroids, endometriosis, pelvic inflammatory disease, benign ovarian cysts, hepatitis, ascites, pleural effusions and lymphangioleiomyomatosis (LAM) 11 12. It has been suggested that Ca-125 is synthesised in the mesothelial cells as a stress response to either fluid congestion (mechanical stress) or cell mediators (inflammatory stress) 13. Howe et al comment on the importance of understanding how these biological mechanisms correlate with a wide range of conditions, for clinicians who are assessing the significance of elevated Ca-125 levels 13.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that Ca-125 is synthesised in the mesothelial cells as a stress response to either fluid congestion (mechanical stress) or cell mediators (inflammatory stress) 13. Howe et al comment on the importance of understanding how these biological mechanisms correlate with a wide range of conditions, for clinicians who are assessing the significance of elevated Ca-125 levels 13. Our case highlights the importance of appreciating and communicating to the patient, the limitations, implications and potential harmful consequences of using this particular ‘gold standard’ tumour marker.…”
Section: Discussionmentioning
confidence: 99%